Comparison of MALDI‐TOF mass spectra with microsatellite length polymorphisms in Candida albicans. (3rd February 2015) - Dhieb, C.; Normand, A. C.; L'Ollivier, C.; Gautier, M.; Vranckx, K.; El Euch, D.; Chaker, E.; Hendrickx, M.; Dalle, F.; Sadfi, N.; Piarroux, R.; Ranque, S.
Abstract : Candida albicans is the most frequent yeast involved in human infections. Its population structure can be divided into several genetic clades, some of which have been associated with antifungal susceptibility. Therefore, detecting and monitoring fungal clones in a routine laboratory setting would be a major epidemiological advance. Matrix‐assisted laser desorption/ionization time‐of‐flight (MALDI‐TOF) mass spectra results are now widely used as bar codes to identify microorganisms in clinical microbiology laboratories. This study aimed at testing MALDI‐TOF mass spectra bar codes to identify clades among a set of C. albicans isolates. Accordingly, 102 clinical strains were genotyped using 10 microsatellite markers and analyzed via MALDI‐TOF mass spectrometry. The mass spectra were compared with a reference spectral library including 33 well‐characterized collection strains, using a Microflex TM system and Biotyper TM software, to test the capacity of the spectrum of a given isolate to match with the reference mass spectrum of an isolate from the same genetic clade. Despite high confidence species identification, the spectra failed to significantly match with the corresponding clade ( p  = 0.74). This was confirmed with the MALDI‐TOF spectra similarity dendrogram, in which the strains were dispersed irrespective of their genetic clade. Various attempts to improve intra‐clade spectra recognition were unsuccessful. In conclusion, MALDI‐TOF mass spectra bar code analysis failed to reliably recognize genetically related C. albicans isolates. Further studies are warranted to develop alternative MALDI‐TOF mass spectra analytical approaches to identify and monitor C. albicans clades in the routine clinical laboratory. Copyright © 2015 John Wiley & Sons, Ltd.